Antique auctions are murder - Klein, Libby (Mystery author) (Klein, Libby (Mystery author). Poppy McAllister mystery, 2022)
B&B owner and gluten-free baker Poppy McAllister, along with her saucy Aunt Ginny, is on the case at the annual Cold Spring Village antique show in Libby Klein's seventh deliciously witty, paleo-themed Poppy McAllister Mystery. When vintage items go up for auction, gluten-free baker and B&B owner Poppy McAllister discovers some people will pay the ultimate price... It's peak summer season at the Butterfly House Bed and Breakfast in Cape May, with tourists fluttering in and out and wreaking enough havoc to rival a Jersey Shore hurricane. Also back in town is Courtney Whipple and his family of antique dealers for the annual Cold Spring Village antique show. Courtney's son Auggie has a unique piece he believes will fetch them a fortune if he can get it authenticated in time--a piece rival dealer Grover Prickle insists was stolen from his store. Poppy and her Aunt Ginny attend the auction, hoping to bid on an armoire for the B&B, and discover a veritable armory for sale--everything from ancient blades and nineteenth century guns to such potential killing devices as knitting needles and a blacksmith hammer. Strangely, they don't see either Auggie or Grover--or the mysterious item they both claim to own. Then during the auction, a body falls out of the very armoire Poppy was hoping to acquire, stabbed through the heart. Now, surrounded by competitive dealers and makeshift weapons, she must find out who turned the auction house into a slaughterhouse...